Making molehills of mountains: Tales of Uttarakhand$1 (Bs climate crisis and an uncertain development models - Edited By Anop, Nautiyal; Raturi, Prerna (Ed.) (Dehradun Bishen Singh Mahendra Pal Singh, 2025)
The second installment in the Making Molehills of Mountains series, this book critically examines the escalating climate crisis in Uttarakhand and the consequences of an unsustainable development model. The year 2024 has been marked by an alarming surge in climate-induced disasters$1 (Brampant forest fires, devastating landslides, torrential rains, and catastrophic cloudbursts. Fast-receding glaciers and a growing number of glacial lakes threaten the delicate balance of the region, putting both people and ecosystems at unprecedented risk. Alongside these environmental challenges, the book scrutinises the rapid loss of green cover, unchecked mountain excavation for large-scale infrastructure projects, dwindling water springs, and the growing menace of land subsidence. It urges a critical re-evaluation of Uttarakhand$1 (Bs current development strategies and highlights the need for a more sustainable path forward. Enriched with expert insights, grassroots narratives, and data-driven analysis, this book is an urgent call to action$1 (Bfor policymakers, environmentalists, and every citizen who cares about the future of the Himalayas. This is more than a book; it is a wake-up call. A must-read for those who wish to understand and address the climate and ecological challenges facing Devbhoomi Uttarakhand.s
Keywords: Geography; Uttarakhand Geography; Demystifying Disasters in Uttarakhand